Aboriginal Family Support Services Inc / together with Aboriginal Communities strengthen families to ensure safe and culturally strong futures for our children and young people. - Aboriginal Family Support Services Inc. (Adelaide, S. Aust.: Aboriginal Family Support Services Inc., 2013)
Website for the Aboriginal Family Support Services Inc. (AFSS); provides assistance and support to Aboriginal people in protecting and preserving their families by way of programs and projects such as: community wellbeing and development, family and community care, volunteer, foster care and family preservation programs, youth accommodation and crisis accommodation, anger management and drug awareness.
Home, Message from the CEO, Organisational chart, Services, Positions vacant, Annual report 2006, Strategic plan, Becoming a carer, Links.
Also known as AFSS.
Previously called Aboriginal Child Care Agency Forum Inc (ACCA)
Title from webpage (viewed 21/8/07)
Board of management include: Kym Mitchell, Ian Davidson, Sharron Williams, Wayne Rigney, Margaret Nelson, Barbara Falla.
Text and images.
Selected for archiving
Keywords: Aboriginal Australians -- Services for -- South Australia -- Adelaide Metropolitan Area; Aboriginal Australians -- Housing -- South Australia; Child welfare - Adoption and fostering; Child welfare - Child / parent separation; Health services - Health programs; Social welfare - Community care; Social welfare - Social work and counselling; Child welfare - Youth services; South Australia (SA)